Project-Based Learning (PjBL) Learning Model on Motivation and Biology Learning Outcomes - Cahyani, Fatehatul; Muhlis, Muhlis; Kusuma, Anindita SHM (Jurnal Pijar Mipa, 2024)
This study aimed to determine whether the Project-Based Learning (PjBL) learning model influenced the motivation and learning outcomes of class XI IPA students at SMA Negeri 1 Kediri. The Nonrandomized Control Group Design quasi-experimental method was used in this study with a quantitative approach. The population in the survey was class XI IPA at SMA Negeri 1 Kediri, and the purposive sampling was not random, so it obtained class MS1 as the experimental class and class MS2 as the control class. The instruments used were questionnaires and multiple-choice test questions. The data obtained were analysed using ancova at a significant level of 5% using the SPSS 25 program. The hypothesis test results in this study showed an influence of the PjBL model on learning motivation and learning outcomes of class XI IPA students at SMAN 1 Kediri with a significance of 0.000 <0.05. The corrected average learning motivation in the experimental class was 162.077, higher than the control class, 139.423. In contrast, the corrected average learning outcomes in the experimental class were 72.193 higher than in the control class, 48.522. Applying the PjBL learning model, students can develop critical thinking skills, creativity and collaboration through project-based assignments that involve active interaction with learning material.